A CROSS SECTIONAL STUDY TO THE ACQUISITION OF ENGLISH WORD TIERS BY INDONESIAN SENIOR HIGH SCHOOL STUDENTS - Euis Rina Mulyani; Iwa Lukmana; Odo Fadloeli (Eltin Journal : Journal of English Language Teaching in Indonesia, 2021)
The present study was aimed to examine English-word tiers acquisition by senior high school students and to identify their strategies to boost their English learning. Its design was cross sectional. To obtain the required data, a test and questionnaire were used. The data were taken from one hundred and five senior high school students who took part voluntarily as the subject of the research. Then, the data were quantified to find frequency and percentage. Furthermore, they were analyzed descriptively. The result of the analysis revealed that the students of the tenth grade tended to acquire the tier I words, followed by tier II and tier III words. In contrast, the order of word-tiers acquisition by students of the eleventh and twelfth grade were tier I, tier III, and tier II respectively. In addition, the data showcased that the majority of the students prefer to use their metacognitive as their strategy to enhance their English learning irrespective of the order of their word tier acquisition. Keywords: Language Learning Strategies, Second Language Acquisition, Word tiers